2021
DOI: 10.1002/jcp.30388
|View full text |Cite
|
Sign up to set email alerts
|

Roles and mechanisms of YAP/TAZ in orthodontic tooth movement

Abstract: Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) are transcriptional coactivators encoded by paratactic homologous genes, shuttle-crossing between cytoplasm and nucleus to regulate the gene expression and cell behavior and standing at the center place of the sophisticated regulatory networking of mechanotransduction. Orthodontic tooth movement (OTM) is a process in which extracellular mechanical stimuli are transformed into intracellular biochemical signals to regulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…F-actin staining showed that LIPUS affected cytoskeletal structural through EphrinB2/EphB4. Hippo pathway is a mechanical stress sensing pathway closely related to the cytoskeleton; participates in the modulation of periodontal homeostasis (Deng et al, 2021). It has been reported that PDLCs sense and respond to mechanical forces during OTM with YAP (Huelter-Hassler et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…F-actin staining showed that LIPUS affected cytoskeletal structural through EphrinB2/EphB4. Hippo pathway is a mechanical stress sensing pathway closely related to the cytoskeleton; participates in the modulation of periodontal homeostasis (Deng et al, 2021). It has been reported that PDLCs sense and respond to mechanical forces during OTM with YAP (Huelter-Hassler et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has also demonstrated the roles and mechanisms of the YAP/TAZ pathway in the orthodontic force transduction. YAP and TAZ are capable of reading mechanical cues, such as shear stress, cell shape, and extracellular matrix rigidity, and stimulate downstream cellular activity ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that cells exhibit various biological reactions when exposed to different forces ( Huang et al, 2018 ), including mechanical forces such as continuous or intermittent compression forces, fluid shear force, mechanical vibration, cyclic tension stress, and static tensile strain ( Chen et al, 2021 ; Qin et al, 2021 ; Wu et al, 2021 ; Shi et al, 2022 ; Sun et al, 2022 ; Manokawinchoke et al, 2023 ). Mechanical force–induced OTM leads to a series of cell proliferation, differentiation, and apoptosis in periodontal tissues ( Deng et al, 2021 ). Periodontal ligament fibroblasts (PDLFs, the main cellular component of PDLCs, also known as PDLCs ( Li et al, 2021 )) provide the biological basis for periodontal soft tissue remodeling through myofibroblast differentiation.…”
Section: Yap and Taz Regulate Periodontal Homeostasis And Remodelingmentioning
confidence: 99%